Acculturation of International Single Students of Higher Education in the Philippines: A Phenomenological Study - Godwin Kato; Istiarti Berci Sarempaa; Naw Ei Phyu Sin Lay; Prema Gaikwad (Pan-African Journal of Education and Social Sciences)
International students move with fractions of their cultural heritage. When they enter a new country, they often encounter a mismatch between their culture and the host culture. In adapting to a new culture, such students experience acculturation. Several studies have been conducted on acculturation. However, knowledge and methodology gaps were found regarding the acculturation of single students in higher education. This study aimed to explore the lived experiences of international acculturated single students of higher education in Philippine international schools. The study is based on Berry’s acculturation model, which involves assimilation, integration, separation, and marginalization. Moreover, hermeneutic phenomenology was utilized to describe and interpret the participants’ experiences. Purposive sampling and maximal variation were used to select the four participants from two faith-based universities. Data was collected through in-depth interviews and visual representations. Based on the findings, acculturation is an eye-opening and identity search process embodying comparative support and continuous inquiry contexts. Participants viewed acculturation as a learning occasion requiring constant change. The findings portray several episodes of cultural preservation, engagement, and voluntary integration consistent with Berry’s acculturation model.